Digitalisasi Kebudayaan Keraton Kanoman Cirebon - Ibnu Amal Fadhilah; Irland Fardani (UNISBA Press, 2022)
Abstract. Keraton Kanoman is one of the most historical cultural heritages in Cirebon City. Currently, the Canoman Palace still does not have an introduction media other than social media such as Instagram, Facebook, and Youtube. The purpose of this study is to design and create an android-based digital application. The application is a form of innovation in the digitization of culture at the Cirebon Canoman Palace. The benefit of this research is to make it easier for people to get to know the culture in the Cirebon Canoman Palace. In addition, this research can also be an innovation in the application of Smart City in Cirebon City, especially in the field of tourism. This research uses qualitative methods. Data or sample collection is carried out using four ways, namely observation, documentation, interviews, and literature studies. The data obtained is then processed to be packaged in a digital application. In designing and making applications, the Agile method is used which consists of six stages, namely Planning, Implementation, Testing, Documentation, Deployment, and Maintenance. Application creation is done by utilizing Android Studio software. The scope of this study is the Cirebon Canoman Palace. In the research conducted, there were four categories of data used, namely building sites, palace history, heirloom objects, as well as customs and rituals. The result of the study is an android-based digital application called DIGICIREBON. The application has several features that display building sites, heirloom objects, palace history, as well as customs and rituals. Each of these features comes with a description, photos, and videos. The compiled application is interactive with the availability of rating and review features. Abstrak. Keraton Kanoman merupakan salah satu cagar budaya yang sangat bersejarah di Kota Cirebon. Saat ini, Keraton Kanoman masih belum memiliki media pengenalan selain media sosial seperti Instagram, Facebook, dan Youtube. Tujuan dari penelitian ini adalah untuk merancang dan membuat sebuah aplikasi digital berbasis android. Aplikasi tersebut merupakan bentuk dari inovasi dalam digitalisasi kebudayaan di Keraton Kanoman Cirebon. Manfaat penelitian ini adalah untuk memudahkan masyarakat untuk mengenal kebudayaan yang ada di Keraton Kanoman Cirebon. Disamping itu, penelitian ini juga dapat menjadi sebuah inovasi dalam penerapan Smart City di Kota Cirebon khususnya pada bidang pariwisata. Penelitian ini menggunakan metode kualitatif. Pengambilan data atau sampel dilakukan menggunakan empat cara yaitu observasi, dokumentasi, wawancara, dan studi pustaka. Data yang didapat selanjutnya diolah untuk dikemas dalam sebuah aplikasi digital. Dalam perancangan dan pembuatan aplikasi, digunakan metode Agile yang terdiri dari enam tahap yaitu Planning, Implementasi, Testing, Dokumentasi, Deployment, dan Maintenance. Pembuatan aplikasi dilakukan dengan memanfaatkan software Android Studio. Lingkup dari penelitian ini adalah Keraton Kanoman Cirebon. Dalam penelitian yang dilakukan, terdapat empat kategori data yang digunakan yaitu tapak bangunan, sejarah keraton, benda pusaka, serta adat dan ritual. Hasil penelitian merupakan sebuah aplikasi digital berbasis android bernama DIGICIREBON. Aplikasi tersebut memiliki beberapa fitur yang menampilkan tapak bangunan, benda pusaka, sejarah keraton, serta adat dan ritual. Masing-masing fitur tersebut dilengkapi dengan deskripsi, foto, dan video. Aplikasi yang disusun bersifat interaktif dengan tersedianya fitur rating dan ulasan.